2003
DOI: 10.1093/jhered/esg101
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Resistance to Clopyralid and Picloram in Yellow Starthistle (Centaurea solstitialis L.) Is Controlled by a Single Nuclear Recessive Gene

Abstract: The noxious weed yellow starthistle (Centaurea solstitialis L.) can be controlled effectively at the seedling stage with foliar application of the auxinic herbicides picloram or clopyralid. Although resistance to these herbicides is rare, a yellow starthistle biotype resistant to picloram and cross-resistant to clopyralid was observed in 1989 near Dayton, WA, in a pasture that had been subjected to intensive picloram selective pressure. Our objective was to determine the mode of inheritance for this resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 18 publications
0
37
0
1
Order By: Relevance
“…However, an isolated occurrence of field resistance to picolinate auxins has been documented in yellow starthistle (Centaurea solstitialis) and appears to have arisen from heavy localized use of picloram. This resistant biotype carries a recessive mutation (Sabba et al, 2003) that confers selective resistance to picloram and clopyralid, but not to 2,4-D, and it also has normal growth and morphology (Fuerst et al, 1996). Thus, the picloramresistant field biotype appears to have some of the characteristics associated with the mutations that we have identified in Arabidopsis.…”
Section: Relevance To Herbicidal Auxin Resistance and Selectivity In mentioning
confidence: 75%
“…However, an isolated occurrence of field resistance to picolinate auxins has been documented in yellow starthistle (Centaurea solstitialis) and appears to have arisen from heavy localized use of picloram. This resistant biotype carries a recessive mutation (Sabba et al, 2003) that confers selective resistance to picloram and clopyralid, but not to 2,4-D, and it also has normal growth and morphology (Fuerst et al, 1996). Thus, the picloramresistant field biotype appears to have some of the characteristics associated with the mutations that we have identified in Arabidopsis.…”
Section: Relevance To Herbicidal Auxin Resistance and Selectivity In mentioning
confidence: 75%
“…In addition, dicamba resistance in kochia (Kochia scoparia L.; biotypes from Henry, Nebraska) is determined by a single allele with a high degree of dominance (Preston et al 2009). Conversely, a single recessive gene controls clopyralid and picloram resistance in yellow starthistle (Centaurea solstitialis L.) (Sabba et al 2003) and quinclorac resistance in false cleavers (Galium spurium L.) (Van Eerd et al 2004). It has been reported that two additive genes control MCPA resistance in common hempnettle (Galeopsis tetrahit L.) (Weinberg et al 2006).…”
Section: Review Of Auxinic Herbicide Resistance In Weedsmentioning
confidence: 99%
“…The cases of recessive gene inheritance of herbicide resistance are rare and limited to few herbicide chemistries. Not surprisingly, these cases have been reported in primarily self-pollinating species (except picloram and clopyralid resistance in yellow starthistle), and the examples include trifluralin resistance in green foxtail [11], quinclorac resistance in false cleaver [12], picloram and clopyralid resistance in yellow starthistle [13], as well as triallate resistance in wild oats [14].…”
Section: Herbicide Resistance and Weed Managementmentioning
confidence: 99%